2020
DOI: 10.1177/0266666920959367
|View full text |Cite
|
Sign up to set email alerts
|

Technology Acceptance Model and Moodle: A systematic mapping study

Abstract: Moodle is one of the most widely used learning management systems currently and has traditionally been studied through the Technology Acceptance Model. Existing literature is scattered and does not allow us to clearly conclude what characteristics this technological acceptance has as well as its main progress. The study aimed to provide an overview of the scientific literature on the application of TAM in the study of the acceptance and technological use of Moodle through a Systematic Mapping Study (SMS). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 40 publications
2
26
0
5
Order By: Relevance
“…Within education the TAM has been used to assess the acceptance of MOOCs (Alraimi et al 2015;Wu and Chen 2017;Zhou 2016) and learning management systems (Alharbi and Drew 2014;Mafuna and Wadesango 2016;Ngai et al 2007;Van Raaij and Schepers 2008). The first TAM studies concerning Moodle were in 2009 since which time research interest has grown with a peak in (Murillo et al 2020). TAM studies have been drawn from diverse educational contexts.…”
Section: Technology Acceptance Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Within education the TAM has been used to assess the acceptance of MOOCs (Alraimi et al 2015;Wu and Chen 2017;Zhou 2016) and learning management systems (Alharbi and Drew 2014;Mafuna and Wadesango 2016;Ngai et al 2007;Van Raaij and Schepers 2008). The first TAM studies concerning Moodle were in 2009 since which time research interest has grown with a peak in (Murillo et al 2020). TAM studies have been drawn from diverse educational contexts.…”
Section: Technology Acceptance Modelmentioning
confidence: 99%
“…First, it adds to the small number of studies which link personality traits to the TAM (Svendsen et al 2013). Second, the lack of Japan-based research identified by Granic and Marangunic (2019) and Murillo et al (2020) is addressed by providing evidence from the Japanese context using Japanese language instruments. Finally, when technology use is compulsory such as it is within the current study, assessments of intent to use become somewhat redundant as course achievement is heavily dependent upon system use regardless of attitude.…”
Section: Introductionmentioning
confidence: 99%
“…Further, PEoU mediates between PU and IU and enhances PU of technology (Davis, 1989). PU and PEoU have been considered as mediators by studies conducted further in expansion and modification of TAM with additional variables in different contexts such as perceived enjoyment, self-efficacy, subjective norm, social influence and social presence (Ajzen, 2002;Akar and Mardikyan, 2014;Al-Qaysi et al, 2020;Chow et al, 2012;Lee et al, 2003;Legris et al, 2003;Murillo et al, 2020;Teo et al, 1999;Venkatesh et al, 2003Venkatesh et al, , 2012Venkatesh and Bala, 2008;Venkatesh and Davis, 2000). Literature validates TAM in various settings.…”
Section: Literature Reviewmentioning
confidence: 90%
“…One part of the recently carried out TAM studies focused on extending the model by further variables (Al-Emran et al, 2018;Murillo et al, 2021;Scherer and Teo, 2019). By involving further variables, the explanatory power of the basic model can be improved.…”
Section: Moderator Variables In Technology Acceptance Modelmentioning
confidence: 99%